The concept of POLISHNESS in the Polish diaspora discourse (a case study) - Białek, Ewa (Papers in Linguistics, 2025)
The aim of the study is to analyse the concept of POLISHNESS in the Polish diaspora discourse. It presents dictionary meanings of the lexeme polskość ‘Polishness,’ explaining also such terms as Polonia ‘Polish minority’ and diaspora, and then characterizing the Polish diaspora’s discourse. The basic criteria for distinguishing this type of discourse are the subject matter (the situation and activities of the Polish diaspora), the sender, and the receiver (Polish diaspora organizations). The lexeme polskość refers to a set of features typical of Poland and Poles, and it is also associated with Polish origin. The undertaken analysis encompasses texts about the Polish community in Russia. In regard to the Polish diaspora discourse, as established, the pillars of Polishness are: knowing the language, being educated in the language, cultivating traditions and rituals, and faith. The Catholic Church and the clergy have great achievements in the centuries-long work of maintaining Polishness in the East. Nowadays, Polish origin can be a chance for development and better opportunities for the young generation. Members of the diaspora notice the rebirth of Polishness in places which, and among people who, previously lost this bond with the country of their ancestors. Proper names are a symbol of the Polish community, emphasizing the bond between members of the diaspora and the ties with the country of origin, its language, values and culture. The study shows that names of organizations and groups of people often include such proper names components as Polonia, Dom Polski, as well as names of state symbols (e.g. the white eagle) and places important from the point of view of Polish history (e.g. Wawel)